2022
DOI: 10.1111/dmcn.15140
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine neurotransmitters in early epileptic encephalopathies: New insights into pathophysiology and therapy

Abstract: AimTo study neurotransmitter status in children with early epileptic and developmental and epileptic encephalopathy (DEE) and to explore the clinical response to dopaminergic and serotoninergic therapies in a group of patients.MethodTwo hundred and five patients (111 males [54.1.%] and 94 females [45.9%], mean age 10 months at the onset of epilepsy [SD 1 year 1 month], range 0–3 year) with epileptic encephalopathy/DEE were recruited, including those with West syndrome, Ohtahara syndrome, early myoclonic enceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Similar decreases in peripheral tryptophan metabolism had been previously described in plasma of Rett syndrome patients 34 and animal models 42 . Likewise, alterations in tryptophan metabolism had been previously reported in developmental and epileptic encephalopathy patients, in which abnormal concentration of neurotransmitter was identified in 33% of the samples, being 5‐HIAA deficit was the most prevalent alteration (91%) 43 . It has also being studied in other diseases with unclear genetic etiology as diverse as migraine, schizophrenia, suicidality or autism spectrum disorders 44–47 …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar decreases in peripheral tryptophan metabolism had been previously described in plasma of Rett syndrome patients 34 and animal models 42 . Likewise, alterations in tryptophan metabolism had been previously reported in developmental and epileptic encephalopathy patients, in which abnormal concentration of neurotransmitter was identified in 33% of the samples, being 5‐HIAA deficit was the most prevalent alteration (91%) 43 . It has also being studied in other diseases with unclear genetic etiology as diverse as migraine, schizophrenia, suicidality or autism spectrum disorders 44–47 …”
Section: Discussionsupporting
confidence: 79%
“…42 Likewise, alterations in tryptophan metabolism had been previously reported in developmental and epileptic encephalopathy patients, in which abnormal concentration of neurotransmitter was identified in 33% of the samples, being 5-HIAA deficit was the most prevalent alteration (91%). 43 It has also being studied in other diseases with unclear genetic etiology as diverse as migraine, schizophrenia, suicidality or autism spectrum disorders. [44][45][46][47] On the other side, although not neurotransmitter-producing, the kynurenine pathway plays essential roles in cell function: it has a key function in energy metabolism by regulation of the coenzyme nicotinamide adenine dinucleotide (NAD+) 48 and has been implicated in the process of inflammation, 49,50 along with the neuroprotective role of kynurenic acid, an intermediate metabolite of the kynurenine pathway that acts as an antagonist to the N-methyl-D-aspartate receptors (NMDARs).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, PTZ-treated groups showed a significant increase ( p < .05) in brain 5-HT and 5-HIAA metabolite concentrations with a reduction in 5-HT level in the hippocampus after MQLE co-supplementation following PTZ administration, suggesting a restoration of spatial learning and memory system. Therefore, the extent of toxicity induced by PTZ may be sufficient to alter the homeostatic state of the growing complex neuronal system (Giachello & Baines, 2017; Juliá-Palacios et al, 2022) leading to integrated neurobiological functions and behavioral responses specifically related to alteration of 5-HT like neurotransmitter and its metabolite (5-HIAA). Although large number of models available for screening anticonvulsant activity, we used PTZ (ip) methods for direct assessment of antiepileptic effects of MQLE on nervous system function.…”
Section: Discussionmentioning
confidence: 99%
“…Monoamines are a representative group of NTs with clinical significance in motor functions, emotional responses, motivations, and behavioral functions [ 3 , 56 ]. These substances are synthesized from presynaptic neurons and bind to the corresponding receptors on the postsynaptic membrane in order to exert their functions.…”
Section: Neurotransmittersmentioning
confidence: 99%
“…or catechol-O-methyltransferase (EC 2.1.1.6) or undergoes reuptake into the presynaptic terminal by monoamine transporters [ 11 ]. Severe neurological diseases (e.g., AD, PD, HD, schizophrenia) can occur when this equilibrium is dysregulated [ 56 , 57 ]. Thus, given their importance, the most representative NTs of this class are individually described in the next paragraphs.…”
Section: Neurotransmittersmentioning
confidence: 99%